Magnetically sensitive radical photochemistry of non-natural flavoproteins - Zollitsch, TM; Timmel, CR; Hore, PJ; Jarocha, L; Bialis, C; Henbest, KB; Kodali, G; Dutton, PL; Moser, CC; Mackenzie, SR (American Chemical Society, 2018)
It is a remarkable fact that ∼50 μT magnetic fields can alter the rates and yields of certain free-radical reactions and that such effects might be the basis of the light-dependent ability of migratory birds to sense the direction of the Earth’s magnetic field. The most likely sensory molecule at the heart of this chemical compass is cryptochrome, a flavin-containing protein that undergoes intramolecular, blue-light-induced electron transfer to produce magnetically sensitive radical pairs. To learn more about the factors that control the magnetic sensitivity of cryptochromes, we have used a set of de novo designed protein maquettes that self-assemble as four-α-helical proteins incorporating a single tryptophan residue as an electron donor placed approximately 0.6, 1.1, or 1.7 nm away from a covalently attached riboflavin as chromophore and electron acceptor. Using a specifically developed form of cavity ring-down spectroscopy, we have characterized the photochemistry of these designed flavoprotein maquettes to determine the identities and kinetics of the transient radicals responsible for the magnetic field effects. Given the gross structural and dynamic differences from the natural proteins, it is remarkable that the maquettes show magnetic field effects that are so similar to those observed for cryptochromes.